2011
DOI: 10.1186/1745-6215-12-92
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of the effects of Exercise Training on Left Ventricular Remodeling Following Myocardial Infarction: Start early and go longer for greatest exercise benefits on remodeling

Abstract: BackgroundThe effects of variations in exercise training on Left ventricular (LV) remodeling in patients shortly after Myocardial Infarction (MI) are important but poorly understood.MethodsSystematic review incorporating meta-analysis using meta-regression. Studies were identified via systematic searches of: OVID MEDLINE (1950 to 2009), Cochrane Central Register of Controlled Trials (1991 to 2009), AMED (1985 to 2009), EMBASE (1988 to 2009), PUBMED (1966 to 2009), SPORT DISCUS (1975 to 2009), SCOPUS (1950 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(117 citation statements)
references
References 38 publications
3
107
1
6
Order By: Relevance
“…Researches has shown that in order to achieve the maximum cardioprotection benefits of exercise and prevent adverse LV remodeling, post-MI patients should start aerobic exercise for about 1 week after discharge from the hospital and continue for longer duration (approx. 6 months) (8). Therefore, one of the reasons for inconsistent results of the present study with previous ones is probably less duration of training following MI.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Researches has shown that in order to achieve the maximum cardioprotection benefits of exercise and prevent adverse LV remodeling, post-MI patients should start aerobic exercise for about 1 week after discharge from the hospital and continue for longer duration (approx. 6 months) (8). Therefore, one of the reasons for inconsistent results of the present study with previous ones is probably less duration of training following MI.…”
Section: Discussioncontrasting
confidence: 88%
“…However, the results of research about the effects of exercise on post-MI cardiac morphological remodeling is contradictory. For example, Haykowsky et al (2011) reported that exercise training after infarction (started 1 week after MI) improved LV remodeling (8). However, Batista et al (2013), in assessment of effects of three-month endurance exercise training, which started 5 and 21 days after MI, reported that the infarct size was not different in experimental groups compared with control group (6).…”
Section: Introductionmentioning
confidence: 99%
“…In a metaregression analysis, Haykowsky et al reported that patients who started exercise training earlier post-MI had greater beneficial effects on left ventricular remodeling (increased ejection fraction and decreased end diastolic and systolic volumes). 41 Improved left ventricular remodeling may in part explain the underlying mechanism for greater improvement in VȮ 2peak and resting heart rate for those who started CR earlier in the current study. Also, if later entry to CR was a patient choice, this may be a proxy for lack of motivation to engage in lifestyle change and thus a mediator of less favorable change in VȮ 2peak and body composition.…”
Section: Consequences Of Longer Wait Timesmentioning
confidence: 75%
“…Starting within this time frame has been shown to be both safe and feasible [19][20][21][22] as well as improving patient uptake and adherence [23] . The gains from early cardiac rehabilitation also include the potential to reduce unplanned readmissions early in the discharge period (within 30 days) thus yielding significant cost savings.…”
Section: Evidencementioning
confidence: 99%